(untitled) (Journal of Environmental Microbiology and Toxicology, 2021)
Codeine-containing cough syrup (CCS) is one of the most abused drugs in the world especially among the youths. However, there is need to study the nephrotoxic effect associated with oral administration of the drug and to ascertain its effect on the kidney. Consequently, understanding the renal abnormalities in chronic use of CCS will be crucial for effective development of interventions. This study assessed the nephrotoxic effect associated with oral administration of codeine-containing cough syrup (Tutolin with Codeine) in albino rats, using the level of creatinine, urea, sodium, potassium and chloride ions as biomarker in the serum of albino rats. The rats were administered orally with Tutolin and Codeine at a dose of 80mg/kg, 160mg/kg, 240 mg/kg and 320mg/kg body weight. After three weeks of oral administration of the syrup to all the groups, there was no difference (P> 0.05) in the levels of sodium ion, chloride ion and creatinine among all the study groups and levels of urea and potassium ion in the group administered with 80 mg/kg, 160 mg/kg and 240 mg/kg body weight of tutolin with codeine compared with the control. After three weeks of oral administration of 80 mg/kg, 160 mg/kg, 240 mg/kg and 320 mg/kg body weight tutolin with codeine cough syrup, urea and potassium ion concentrations were higher (p<0.05) in group given 320mg/kg body weight of tutolin with codeine cough syrup compared with the control. This suggests that at higher doses, tutolin with codeine containing cough syrup may have effect on the kidney.